2018
DOI: 10.1101/254904
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide translating mRNA analysis following ketamine reveals novel targets for antidepressant treatment

Abstract: Low-dose ketamine is an efficacious antidepressant for treatment-resistant unipolar and bipolar depressed patients. Major Depression Disorder patients receiving a single infusion report elevated mood within two hours, and ketamine's antidepressant effects have been observed as long as seven days post-treatment. In light of this remarkable observation, efforts have been undertaken to "reverse-translate" ketamine's effects to understand its mechanism of action. Major advances have been achieved in understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
2
2
0
Order By: Relevance
“…In contrast, our RNA seq data revealed a significant increase in the expression of VIPR2 in the PLc. This extends a previous finding showing this following acute ketamine administration [76], to indicate that VIPR2 expression is also increased after sub-chronic ketamine administration. VIPR2 is expressed in somatostatinpositive interneurons and increases excitability of these interneurons [76].…”
Section: Proposed Mechanism Of Action Of Ketamine On Dopamine Synthessupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, our RNA seq data revealed a significant increase in the expression of VIPR2 in the PLc. This extends a previous finding showing this following acute ketamine administration [76], to indicate that VIPR2 expression is also increased after sub-chronic ketamine administration. VIPR2 is expressed in somatostatinpositive interneurons and increases excitability of these interneurons [76].…”
Section: Proposed Mechanism Of Action Of Ketamine On Dopamine Synthessupporting
confidence: 90%
“…This extends a previous finding showing this following acute ketamine administration [76], to indicate that VIPR2 expression is also increased after sub-chronic ketamine administration. VIPR2 is expressed in somatostatinpositive interneurons and increases excitability of these interneurons [76]. This finding highlights that other GABAergic interneurons may be affected by sub-chronic ketamine treatment and the need for further work to determine if expression changes in these interneurons, or others that we were not able to measure such as calretinin positive interneurons, contribute to ketamine's effects on dopamine regulation and behaviour.…”
Section: Proposed Mechanism Of Action Of Ketamine On Dopamine Synthessupporting
confidence: 90%
“…Ketamine may exert its antidepressant effects via one of its metabolites, (2R,6R)-HNK 9 , which may act as an inhibitor of NMDA (N-methyl-d-aspartate) receptors at certain concentrations 9,15,16 . Ketamine and (2R,6R)-HNK activate mTORC1 signalling and protein synthesis in the prefrontal cortex (PFC) and hippocampus (HPC) 7,10,11,[17][18][19][20] . Furthermore, in rodents, the antidepressant response to ketamine and (2R,6R)-HNK is blocked by infusion of rapamycin, an allosteric inhibitor of mTORC1, into the PFC 10,11 .…”
mentioning
confidence: 99%
“…KLF2 protein is implicated in lung development, embryonic erythropoiesis, epithelial integrity, T-cell viability and adipogenesis (31). Another study by Miller et al (32) was performed using ribosome-bound mRNA footprinting and deep sequencing, and confirmed that initiation of protein synthesis is a defining feature of antidepressant dose ketamine in mice; with the use of GO analysis, vasoactive intestinal peptide receptor 2 gene was identified as a potential target for antidepressant action. In the current study, Klf2 was involved in more pairs in the PPI network of DEGs in the striatum samples treated with ketamine, phencyclidine or memantine compared with normal samples.…”
Section: Discussionmentioning
confidence: 92%